Comparison of medium-vacuum and plasma-activated low-temperature wafer bonding - Tan, Cher Ming (2013)
Two low-temperature wafer bonding methods, namely the medium-vacuum level wafer bonding (MVWB) and plasma-activated wafer bonding (PAWB), are performed. After low-temperature annealing(500°C) for a short time (<5h) , the bond strength of these two low-temperature methods is improved as compared to the conventional air wafer bonding. The bond efficiency of MVWB is found to be better than the conventional air wafer bonding, but PAWB contains more bubbles. The qualitative mechanisms of these two low-temperature wafer bonding methods are proposed.